The Teacher and Teaching Polish as a Second Language in the Contemporary Educational Reality - Gębal, Przemysław E. (Kultura-Społeczeństwo-Edukacja, 2019)
An increasing number of immigrants arrive in our country, not all of whom treat Poland only as a transit stop on their way to wealthier countries of the Western Europe. What this means for the Polish society, with its cultural and linguistic homogeneity, is a direct confrontation with cultural and religious otherness, represented by the settling newcomers. Unfortunately, the educational establishments are not sufficiently prepared to take in new students with migration backgrounds. The entire situation also poses an enormous challenge for polonistic glottodidactics, actively present in the process of acculturation of the foreigners. The undertaken actions are primarily focused on organising and conducting classes in Polish as a second language. An important element to ensure the proper execution of the discussed process is the education of teachers, the presentation of which is a principal goal of this text.